Effect of biofertilizer and wheat straw biochar application on nitrous oxide emission and ammonia volatilization from paddy soil. (15th April 2021) - Sun, Haijun; Zhang, Yu; Yang, Yiting; Chen, Yudong; Jeyakumar, Paramsothy; Shao, Qianlan; Zhou, Youfeng; Ma, Meng; Zhu, Ruiqi; Qian, Qiawei; Fan, Yuerong; Xiang, Shujie; et al.
Abstract: Biofertilizer can improve soil quality, especially the microbiome composition, which potentially affect soil nitrogen (N) cycling. However, little is known about the responses of nitrous oxide (N2 O) emission and ammonia (NH3 ) volatilization from biochar-amended paddy soil to the biofertilizer application. Therefore, we conducted a soil column experiment using four 240 kg N ha −1 (equivalent to 1.7 g N pot −1 ) treatments consisting of biofertilizer (3 t ha −1, equivalent to 21.2 g pot −1 ), biochar (7.5 t ha −1, equivalent to 63.6 g pot −1 ), and a mixture of biofertilizer and biochar at the same rate and a control (CK). The results showed that the N2 O emissions and NH3 volatilizations were equivalent to 0.15–0.28% and 18.0–31.5% of rice seasonal N applied to the four treatments, respectively. Two treatments with biofertilizer and biochar individual amendment significantly increased ( P  < 0.05) the N2 O emissions to same degree by 30.2%, while co-application of biochar and biofertilizer further increased the N2 O emission by 74.4% compared to the control. The higher N2 O emission was likely attributed to the increased gene copies of AOA, nirK, and nirS . Applying biofertilizer significantly increased ( P  < 0.05) NH3 volatilization by 24.7% relative to the control, while applying biochar had no influence on NH3 volatilization. Co-application of biofertilizer and biochar significantly decreased ( P  < 0.05) NH3 volatilization by 12.3% compared to the control. Overall, the net global warming potential based on NH3 and N2 O in current study increased by 13.0–26.0% in both the individual- and co-application of biofertilizer and biochar. Interestingly, both individual- and co-applications of biofertilizer and biochar increased the rice grain yield by 16.5–38.3%. Therefore, applications of biofertilizer and biochar did not increase the GHGI. Particularly, the co-applying of them significantly lowered ( P  < 0.05) the GHGI by 15.2%. In conclusion, biofertilizer and biochar should be co-applied to achieve the goals of environment protection and food security. Graphical abstract: Image 1 Highlights: Systematic evaluation of the effects of biofertilizer and/or biochar on NH3 and N2 O losses in paddy soil. Biofertilizer individual application stimulate both NH3 volatilization and N2 O emission. Co-applying biofertilizer and biochar suppresses the NH3 volatilization by 12.3%. Biofertilizer and/or biochar increase rice grain yield by 16.5%–38.3%. GHGI was mitigated by 15.2% under co-applying biofertilizer and biochar treatment.